Method for measuring thickness of inhibition layer of zinc layer of hot-dip galvanized steel sheet

Through the combination of scanning electron microscope and energy spectrometer, the difficulty of measuring the thickness of the hot-dip galvanized steel plate is solved, and accurate and convenient measurement of the thickness of the suppression layer is achieved.

CN119715642APending Publication Date: 2025-03-28BENGANG STEEL PLATES CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411646575.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, there are difficulties in measuring the thickness of the hot-dip galvanized steel plate suppression layer, including the difficulty in distinguishing the location of the suppression layer and the morphology is chaotic when the corrosion method is incorrect, so it is impossible to accurately measure it.

Method used

The combination of scanning electron microscope and energy spectrometer is used to perform thermal inlay treatment and grinding of hot-dip galvanized steel plate samples, and the joint parts of the zinc layer and the steel base are observed by scanning the energy spectrometer surface to measure the thickness of the suppression layer.

Benefits of technology

It realizes simple and convenient measurement of the thickness of the suppression layer, avoids difficulties in the corrosion process, and the measurement results are intuitive and accurate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119715642A_ABST
    Figure CN119715642A_ABST
Patent Text Reader

Abstract

The invention discloses a method for measuring the thickness of an inhibition layer of a zinc layer of a hot-dip galvanized steel sheet, which comprises the following steps: cutting a sample into a metallographic sample size, carrying out hot inlaying treatment on the sample by using a conductive inlaying material, taking the cross section of the sample as a detection surface, and grinding the detection surface after inlaying; according to the prepared sample, the thickness of the inhibition layer is measured in a mode of combining a scanning electron microscope and an energy dispersive spectrometer. According to the method, the sample does not need to be corroded, the measurement method is simple and easy to implement, the display effect is visual, and the distribution uniformity of the inhibition layer can be visually observed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steel material detection, and in particular relates to a method for measuring the thickness of a zinc layer inhibition layer of a hot-dip galvanized steel plate. Background Art

[0002] In the hot-dip galvanizing process, adding 0.15% to 0.2% aluminum to the zinc liquid changes the composition and structure of the zinc coating, and forms a thinner Fe-Al layer on the interface between the pure zinc layer and the steel substrate. This thin Fe-Al layer (less than 1um) is called an inhibition layer. The inhibition layer can improve the adhesion of the zinc coating. If the zinc liquid does not contain Al, the Fe-Zn phase formed by Zn and Fe in the coating grows very fast and has poor adhesion, so that the hot-dip galvanized sheet may cause the coating to peel off during deformation. Adding a certain amount of Al to the zinc liquid can effectively inhibit the growth of the Fe-Zn phase in the early stage of galvanizing, thereby improving the adhesion of the coating. The measurement of the depth of the inhibition layer is necessary in the research process of the galvanizing process. Currently, there are great difficulties in measuring the depth of the inhibition layer.

[0003] In the prior art, if the conventional sample cross-section measurement method is used to measure the thickness of the inhibition layer of hot-dip galvanized samples, the following problems exist: First, after the sample cross-section of the test sample is prepared, it is difficult to distinguish the location of the inhibition layer. Second, if the test surface is corroded, due to the presence of the surface zinc layer, it is easy for the zinc layer to corrode quickly and the steel substrate to corrode slowly during corrosion, resulting in a stepped morphology with a high steel substrate and a low zinc layer, which causes the test surface to be not on the same test surface; at the same time, if the corrosion method is incorrect, the corrosion morphology is chaotic and the location of the inhibition layer cannot be distinguished. For example, the patent with publication number CN106092709A, "A method for preparing a sample for detecting the characteristics of the interface inhibition layer of a hot-dip galvanized sheet and a corresponding preparation device", requires a special device, including a corrosion reaction device and a sample constant speed descending device, which slowly and continuously immerses the galvanized sheet strip sample into the corrosive solution at a constant speed μ for corrosion until the sample head is excessively corroded and the metallic luster of the substrate is clearly revealed; this detection method is mainly a method for observing the morphology of the inhibition layer, which has nothing to do with the measurement of the thickness of the inhibition layer. The patent with publication number CN113514528A discloses "a method for measuring the density of the inhibition layer of hot-dip galvanized sheet", which uses the hot-dip galvanized sheet sample to be tested as the working electrode, and places it and the auxiliary electrode in an electrolyte, and energizes the working electrode and the auxiliary electrode for constant current polarization; during the polarization process, a polarization curve is recorded with the polarization time as the horizontal coordinate and the polarization voltage corresponding to the polarization time as the vertical coordinate; the polarization curve is differentiated to obtain the derivative curve; according to the derivative curve, the density of the inhibition layer of the hot-dip galvanized sheet sample to be tested is obtained; the detection index in this patent is the density of the inhibition layer, which is different from the thickness of the inhibition layer, and its detection method is relatively difficult. Summary of the invention

[0004] In order to overcome the defects of the prior art, the present invention aims to form a testing method, by which the thickness of the inhibition layer can be simply and conveniently detected.

[0005] In order to achieve the above-mentioned purpose of the invention, the present invention provides a method for measuring the thickness of the zinc layer inhibition layer of a hot-dip galvanized steel plate, which overcomes the difficulties encountered in the process of measuring the thickness of the inhibition layer by combining a scanning electron microscope with an energy spectrometer, making the measurement of the thickness of the inhibition layer simple and easy; the measuring method comprises the following steps:

[0006] Preparation of S1 sample: Cut the sample into the size of metallographic sample, and use conductive mounting material to perform hot mounting on the sample. The cross section of the sample is the test surface. After mounting, grind the test surface with dry sandpaper.

[0007] Furthermore, the cross-section sample of the hot-dip galvanized steel plate to be tested is subjected to hot embedding treatment, and the hot embedding material adopts conductive embedding material; the hot embedding treatment is to place samples with higher hardness in front and behind the embedded zinc layer sample as edge protection materials, and a certain gap is left between the protection material and the zinc layer sample.

[0008] Furthermore, during the sample preparation process, in order to ensure that the zinc layer morphology is intact, the grinding direction is always kept in the same direction, and 180#, 320#, 500#, 800#, and 1200# sandpaper are used to grind the samples respectively. During the grinding process, the morphology of the zinc layer needs to be observed under an optical microscope to confirm that the zinc layer has not fallen off. After grinding, polish with a dry velvet polishing cloth.

[0009] S2. Sample testing: The sample prepared in step S1 is subjected to the measurement of the thickness of the inhibition layer by combining a scanning electron microscope with an energy dispersive spectrometer. The specific sample testing steps include:

[0010] ① Place the sample prepared in step S1 under SEM to observe the bonding area between the zinc layer and the steel base;

[0011] ②After selecting the observation area, adjust the magnification to 5000× to make the image clear; at the same time, make the junction between the zinc layer and the steel base located in the middle of the observation image;

[0012] ③ Turn on the spectrometer, select surface scanning, take the junction of the zinc layer and the steel base as the middle axis, select a rectangular area that spans part of the zinc layer and part of the steel base. Since the thickness of the inhibition layer is generally less than 1μm, the selected area must have space to accommodate the inhibition layer area;

[0013] ④ Scan the selected area using an energy spectrometer;

[0014] ⑤ Find the images with high Al content in the surface scan. It can be observed that as the number of scan frames increases, a clear area with high Al content appears in the middle of the image, and the thickness distribution in this area is relatively uneven;

[0015] ⑥ After determining the surface scanning image, measure the thickness of the inhibition layer in combination with the image ruler.

[0016] The formation of the inhibition layer is mainly due to the addition of Al in the zinc pool, which preferentially reacts with Fe on the surface of the steel plate to form a Fe-Al phase. The formation of the Fe-Al phase will cause the aggregation of Al elements on the one hand, and on the other hand, it will cause Al-poor areas to appear around the Fe-Al phase. Therefore, after scanning, Al elements are aggregated along the surface of the steel base in a lamellar distribution, which can be considered as the area where the inhibition layer is located. In this way, the thickness of the inhibition layer can be measured by its morphology combined with the image scale.

[0017] Furthermore, the inhibition layer thickness is measured based on the measurement points being clustered and continuous.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention uses a scanning electron microscope combined with an energy spectrum analyzer to measure the thickness of the inhibition layer, which does not require the sample to be corroded, thus avoiding the trouble caused by the difficulty of corroding the sample. The measurement method is simple and easy, the display effect is intuitive, and the uniformity of the inhibition layer distribution can be intuitively observed. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the position of the zinc layer after the sample is prepared in the example;

[0021] Figure 2 The distribution diagram of Al content in the scanning area of ​​the hot-dip galvanized steel plate under SEM and the surface scanning of the energy spectrum analyzer is shown in the embodiment;

[0022] Figure 3 The scanning area of ​​the zinc layer and the Al content distribution diagram (5000×) in the embodiment. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with specific examples, but the present invention is not limited in any way. To avoid redundant description, the raw materials in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.

[0024] A method for measuring the thickness of a zinc layer inhibition layer of a hot-dip galvanized steel plate, the method comprising the following steps:

[0025] S1 Sample preparation: Cut the sample into the size of the metallographic sample, use conductive mounting material to perform hot mounting on the sample, the cross section of the sample is the test surface, and the test surface is ground after mounting;

[0026] S2 Sample detection: The sample prepared in step S1 is subjected to measurement of the thickness of the inhibition layer by combining a scanning electron microscope with an energy dispersive spectrometer.

[0027] The matters not described in the following embodiments are the same as the description of the above specific implementation methods.

[0028] Example

[0029] A method for measuring the thickness of the zinc layer inhibition layer of a hot-dip galvanized steel plate. The test process takes the corrosion of a DC51D+Z hot-dip galvanized steel plate sample as an example. The specific detection steps are as follows:

[0030] Preparation of S1 sample: Cut the sample into the size of metallographic sample, and use conductive mounting material to perform hot mounting on the sample. The cross section of the sample is the test surface. After mounting, grind the test surface with dry sandpaper.

[0031] During the hot inlay process, samples with higher hardness are placed before and after the zinc layer sample as edge protection materials, and a 0.5mm wide gap is left between the protection material and the zinc layer sample. During the sample preparation process, in order to ensure that the zinc layer morphology is intact, the grinding direction is always kept in the same direction, and 180#, 320#, 500#, 800#, and 1200# sandpaper are used to grind the sample respectively; after grinding, the sample surface is cleaned with alcohol, and after drying, the sample is polished with a dry velvet polishing cloth. After the sample is prepared, it is observed under a microscope to confirm that the zinc layer has not fallen off.

[0032] S2 Sample testing: The sample prepared in step S1 is Figure 1 As shown, Figure 1 The morphology of the zinc layer after the sample is prepared in the example; the thickness of the inhibition layer is measured by combining a scanning electron microscope with an energy dispersive spectrometer; the specific sample detection steps include:

[0033] ① Place the sample prepared in step S1 under SEM to observe the bonding area between the zinc layer and the steel base;

[0034] ②After selecting the observation area, adjust the magnification to 5000× to make the image clear; at the same time, make the junction between the zinc layer and the steel base located in the middle of the observation image;

[0035] ③ Turn on the spectrometer, select surface scanning, take the junction of the zinc layer and the steel base as the middle axis, select a rectangular area that spans part of the zinc layer and part of the steel base. Since the thickness of the inhibition layer is generally less than 1μm, the selected area must have space to accommodate the inhibition layer area;

[0036] ④ Use the energy spectrometer to scan the selected area, such as Figure 2 As shown, Figure 2 This is the scanning area of ​​the hot-dip galvanized steel plate under SEM in the embodiment;

[0037] ⑤ In the surface scanning images, find the images with high Al content. It can be observed that as the number of scanning frames increases, a clear area with high Al content appears in the middle of the image, such as Figure 3 As shown, Figure 3 This is the distribution diagram of Al content scanned by energy spectrum analyzer;

[0038] ⑥ After determining the surface scanning image, measure the thickness of the inhibition layer in combination with the image ruler.

[0039] After capturing the image and confirming the surface scan image and scale, the measurement software is used to measure the area with high and continuous Al distribution. Figure 3 Scanning the image, the thickness distribution of the Al content in this area is relatively uneven. The measurement shows that the thickness of the narrow part of the inhibition layer is 0.4μm, and the wide part is about 0.85μm.

[0040] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for measuring the thickness of the zinc layer inhibition layer of a hot-dip galvanized steel sheet, characterized in that: The measuring method comprises the following steps: S1 Sample preparation: Cut the sample into the size of the metallographic sample, use conductive mounting material to perform hot mounting on the sample, the cross section of the sample is the test surface, and the test surface is ground after mounting; S2 Sample detection: The sample prepared in step S1 is subjected to measurement of the thickness of the inhibition layer by combining a scanning electron microscope with an energy dispersive spectrometer.

2. The measuring method according to claim 1, characterized in that: The hot embedding treatment in step S1 is to place samples with higher hardness in front and behind the embedded zinc layer sample as edge protection materials, leaving a gap between the protection material and the zinc layer sample.

3. The measuring method according to claim 1, characterized in that: The grinding direction in step S1 is always kept in the same direction, and the sample is ground using 180#, 320#, 500#, 800#, and 1200# sandpaper respectively. During the grinding process, the morphology of the zinc layer is observed under an optical microscope, and polishing is performed after grinding.

4. The measuring method according to claim 1, characterized in that: The detection of the sample in step S2 comprises the following steps: ① Place the sample prepared in step S1 under SEM to observe the bonding area between the zinc layer and the steel base; ②After selecting the observation area, adjust the magnification to 5000× to make the image clear; at the same time, make the junction between the zinc layer and the steel base located in the middle of the observation image; ③ Turn on the spectrometer, select surface scanning, take the junction of the zinc layer and the steel base as the middle axis, select a rectangular area that spans part of the zinc layer and part of the steel base. The selected area has space to accommodate the inhibition layer area; ④ Scan the selected area using an energy spectrometer; ⑤ Find the images with high Al content in the surface scan images; ⑥ After determining the surface scanning image, measure the thickness of the inhibition layer in combination with the image ruler.

5. The measuring method according to claim 4, characterized in that: The thickness of the inhibition layer is measured based on the fact that the measurement points are clustered and continuous.

Citation Information

Patent Citations

  • Preparation method and preparation apparatus of hot galvanizing plate interface inhibition layer character detection sample

    CN106092709A

  • Method for measuring compactness of inhibition layer of hot-dip galvanized sheet

    CN113514528A

  • Method for characterizing inhibition layer of galvanized plate

    CN108872285A

  • Metallographic test method for identifying electro-galvanized and hot-galvanized steel products

    CN110057994A

  • Method for representing quality of inhibition layer on section of hot-dip galvanized sheet

    CN117929436A